2019
DOI: 10.7213/1981-4178.2019.17301
|View full text |Cite
|
Sign up to set email alerts
|

Pesquisa de anticorpo anti-Leptospira spp. e anti-Brucella spp. em equinos provenientes da Ilha do Marajó, Pará

Abstract: Pesquisa de anticorpos contra Leptospira spp. e Brucella lisa foi realizada em equinos da raça Marajoara e Puruca provenientes da Ilha do Marajó. Utilizaram-se 57 amostras de soro de equinos de ambos os sexos, diferentes idades e sem sintomatologia clínica de doença causada pelos agentes pesquisados. As amostras forma submetidas ao teste de aglutinação microscópica (MAT) para pesquisa de Leptospira spp. e teste de soroaglutinação rápida em placa com antígeno acidificado tamponado (AAT) para pesquisa de Brucell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…There are only a few studies on the prevalence of brucellosis among working equids. In Brazil, its prevalence has been found to range from 0% to 5.7% (DORNELES et al, 2013;PINHO et al, 2014;ROCHA et al, 2019;RESENDE et al, 2022). In Nigeria, prevalence of 3% has been reported (NJOGA et al, 2018), while in Pakistan, the prevalence was found to reach 20.1% (GUL et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…There are only a few studies on the prevalence of brucellosis among working equids. In Brazil, its prevalence has been found to range from 0% to 5.7% (DORNELES et al, 2013;PINHO et al, 2014;ROCHA et al, 2019;RESENDE et al, 2022). In Nigeria, prevalence of 3% has been reported (NJOGA et al, 2018), while in Pakistan, the prevalence was found to reach 20.1% (GUL et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…There are several infectious diseases that affect horses and can cause great economic losses in this sector and damage to the well-being of animals, including diseases of zoonotic potential such as glanders, leptospirosis and brucellosis (Barcelos et al, 2017;Rocha et al, 2019). In equines, purulent abscess lesions in bursae, ligaments, tendons, synoviums and joints, preferably in the withers are strongly suggestive of brucellosis, and reproductive disorders in this species are rare.…”
Section: Introductionmentioning
confidence: 99%